(untitled) (Revista de Estudos da Linguagem, 2024)
This paper investigates specific manifestations of fictivity, such as the cognitive pattern of discrepant representations (TALMY, 2000), in oral language data collected by Cadilhe (2013) from undergraduate medical classes. More specifically, we use the concept of Fictive Interaction (PASCUAL, 2014), according to which language users use the Conversation Frame to structure thought, grammar and discourse, so as to highlight its potential for application as a communicative teaching and learning strategy. As a methodology, we use the blend of corpus-based and corpus-driven approaches to balance theoretical categories and empiricism. As a result, four formal and functional patterns of fictivity were mapped: fictive question-answer, fictive question, fictive deixis, and fictive direct speech. It was found, especially in teaching speech, that fictivity is often used in discursive moments of argumentation and explanation. However, teacher and students demonstrate to know how to operate with non-true scenarios in order to gain access to effective scenarios that involve medical practice. It is also noted that the phenomenon is a moderating device of teaching and learning, as a communicative strategy that appeals to the Conversation Frame to take advantage of what is most pervasive and entrenched in cognitive and interaction subjects, which is the everyday conversation itself.